Stretching : c - Martin, Suzanne (London : Dorling Kindersley Limited, 2005)
Stretching is the key if you want to stay healthy and supple. This practical head-to-toe guide provides quick home exercises that fit easily into your daily life
Includes bibliographical references and index
Keywords: Exercise for women; Stretching exercises